Measuring the Position of the Mandibular Foramen in Relation to the Dentoalveolar Plane in Pierre Robin Patients: Establishing Safety of the Horizontal Osteotomy. Issue 1 (January 2020) - Do, Nicholas T.; Klement, Kristen A.; Denny, Arlen D.
Abstract : Background: Mandibular distraction with horizontal osteotomy of the ramus and vertical distraction vector has successfully treated airway obstruction in young Pierre Robin patients. Placing the osteotomy just above the dentoalveolar plane can minimize damage to the inferior alveolar nerve. This study maps the position of the mandibular foramen relative to the height of the dentoalveolar plane to demonstrate the safety of this technique in Pierre Robin neonates. Methods: Retrospective review of 3D CT scans of Pierre Robin patients was performed with inclusion criteria: ⩽1 year of age, bilateral micrognathia requiring surgical intervention for airway (ie, tracheostomy versus mandibular distraction), no prior mandible surgery, and pre-operative 3D CT study. Demographic information collected included: age at CT scan, age at surgery, and genetic diagnosis. Using the 3D study of each patient's right mandible, a line at the level of the mandibular dentoalveolar plane was drawn across the lingual surface of the ramus and the distance to the mandibular foramen at a length perpendicular to the dentoalveolar plane line was then measured. Results: Fifteen patients were included in the study (at least 9 Pierre Robin). Average age at time of CT scan was 71.4 days old. The mandibular foramen was below the level of the dentoalveolar plane in all cases at an average distance of 4.7 mm. Average ramus height 46.2±13.4 Conclusions: The dentoalveolar plane was consistently above the mandibular foramen in all patients. Thus, the horizontal corticotomy at a level just above the mandibular dentoalveolar plane spares the inferior alveolar nerve in neonatal Pierre Robin patients undergoing vertical vector mandibular distraction. Abstract : Supplemental Digital Content is available in the text